CTNI-49. PHASE I STUDY OF MGMT-P140K TRANSFECTED HEMATOPOETIC PROGENITOR CELLS COMBINED WITH TMZ/O6BG DOSE ESCALATION FOR NEWLY DIAGNOSED, UNMETHYLATED GLIOBLASTOMA: TOLERANCE AND EVIDENCE OF SURVIVAL BENEFIT. (9th November 2020) - Sloan, Andrew E; Fung, Hua; Reese, Jane; Rgers, Lisa; Murphy, Christopher; Lazarus, Hillard; Dropulic, Boro; Gerson, Stanton
Abstract: INTRODUCTION: GBM has median survival of 12 months despite current SOC therapy. The most important mechanism of TMZ resistance is the O6-methylguanine-DNA methyltransferase (MGMT) gene. The MGMT inhibitor O6-benzylguanine (BG) demonstrated efficacy in depleting MGMT but approach led to unacceptable bone marrow toxicity and has thus been abandoned. We hypothesized that chemoprotection of hematopoietic HPC with an MGMT mutant (MGMT-P140K) characterized by normal methyltransferase activity, coupled with low affinity for BG would maximize anti-tumor response while enabling patients to tolerate TMZ & BG dose escalation with minimal toxicity. A phase I trial was performed to test this hypothesis. METHODS: 10 adults with newly diagnosed MGMT unmethylated, IDH-1 WT, GBM underwent standard surgery and radiation, followed by transplantation with autologous CD34+ HPC transfected with MGMT-P140K using a lentiviral vector. We tested tolerance and efficacy of three different paradigms for conditioning bone marrow and re-infusion of HPC. RESULTS: Treatment was moderately toxic with 3/10 patients suffering grade 3–4 hematologic toxicity; no high grade non-hematologic toxicity was observed. Viral transduction rates ranged from 3–75% and were clearly improved in Arm III utilizing BCNU conditioning and intra-patient dose escalation of TMZ/O6GB. In patients tolerating 3 cycles or more, P140K-MGMT gene markings in peripheral blood and bone marrow cells increased 3-26-fold with only mild (Grade 2–3) myelosuppression consistent with chemo-protection as hypothesized. Median PFS and OS was 24 and 33 months respectfully, and three patients in Arm III were progression free at 36 months with one progression free at 48 months. OS exceeded RPA & Nomogram predicted survival by 3.6-fold, suggesting clinical benefit. Viral insertion site analysis demonstrate no clonal dominance. CONCLUSIONS: P140K-MGMT transfected HPC enables TMZ/ BG dose escalation with acceptable toxicity and increased survival in a small cohort of selected patients. A U-01 funded phase II study is ongoing at UH and NIH.